Law Enforcement Assistance Administration Profile Data, (1968-1978) ([Verlag nicht ermittelbar], 1985)
The Law Enforcement Assistance Administration File (PROFILE) System was designed for the automated storage and retrieval of information describing programs sponsored by the Bureau of Justice Statistics. The two types of data elements used to describe the projects in this file are basic data and program descriptors. The basic data elements include the title of the grant, information regarding the location of the grantee and the project, critical funding dates, the government level and type of grantee, financial data, the name of the project director, indication of the availability of reports, and identification numbers. The program descriptor elements form the program classification system and describe the key characteristics of the program. Key characteristics include subject of the program, primary and secondary activity, whether the program covered a juvenile or adult problem, and what specific crimes, clients, staff, program strategies, agencies, equipment, or research methods were to be used or would be affected by the project.